One Government One Voice? Government Narrative in Crisis Communication during the Pandemic - Andre Noevi Rahmanto (Jurnal the Messenger, 2024)
Introduction: Government public relations ideally conveys policies and regulations in an integrated manner (one government one voice), but in reality there is often different and contradictory information in each government institution, thus confusing the public and hindering the handling of the pandemic. This research answers the question of how the crisis narrative is built by 5 (five) central government institutions in Indonesia through their official websites, whether the narrative tends to be integrated or vice versa.